GEOPOLITIK PERBATASAN KASHMIR STUDI KASUS: PENGARUH KONFLIK INDIA-PAKISTAN TERHADAP KEAMANAN GLOBAL - Fajrin, Ahmad Fariz Ali Muzaki; Tamaela, Meyrill D.G.; Siswatiningrum, Etik (Jurnal Ilmiah Hubungan Internasional Fajar, 2024)
The border conflict between India and Pakistan in the Kashmir region has persisted for over seven decades, making it one of the most complex territorial disputes in the world. This conflict is rooted not only in religious differences and national identity but also in strategic interests tied to the region's abundant water resources and its geostrategic position. The tensions in this area have significantly impacted regional security in South Asia an d h av e f ar -r eac h in g im plic at ion s f or global stability, particularly given the involvement of two nuclear-armed states. This study examines the geopolitical dynamics of the Kashmir border conflict, focusing on factors influencing the dispute, including national interests, the role of non-state actors, and the influence of major powers in the region. Furthermore, it evaluates efforts made by international organizations and other states to mediate the conflict, as well as the challenges encountered in achieving a sustainable and peaceful resolution. Utilizing a multidisciplinary approach, this research aims to provide a comprehensive understanding of how the Kashmir conflict affects global security and proposes multilateral diplomatic strategies as a pathway toward long-term stability. Keywords: Geopolitics, Kashmir, South Asia, Global Security